ANALISIS PERILAKU TERLAMBAT PADA PESERTA DIDIK SMP NEGERI 2 SUNGAI RAYA - Syarifah Runika Umaria; Yuline Yuline; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractLate habit is an action of comming to a place or an event past the agreed time. Thishappens because the school is less firm in implementing the existing rules and as the form of students’ indiscipline. Every student in SMP Negeri 2 Sungai Raya is expected to have a disciplined attitude but in fact, there still can be found late students everyday. In general, this study aims to obtain an overview of "Late Habit of Students at SMP Negeri 2 Sungai Raya". (1) Factors that cause students lateness at SMP Negeri 2 Sungai Raya. (2) The impact that occurs on late students at SMP Negeri 2 Sungai Raya. (3) Efforts done by BK teachers towards late students in SMP Negeri 2 Sungai Raya. The method used in this study was descriptive method and the form of the research was survey research. The subjects in this study were three students and their close friends as well as 2 BK teachers. This study used qualitative approach. Data collection techniques used were observation, interview, and documentation. Based on the results of the study, the factors causing students to be late were (1) they usually woke up late, (2) They were lack of preparation for class activities, (3) They had problem with their vehicle. The impact of being late is (1) low grades, (2) Relationships with teachers were disrupted, (3) Relationships with classmates were disrupted. The efforts made by the BK teachers in solving these “late habit” cases were (1) giving sanctions or punishments, and (2) calling the parents. Keywords: Students, Habit, Late